2005
DOI: 10.1007/11590019_10
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Knowledge Through a Method Framework in an Electronic Process Guide

Abstract: Abstract.A key leverage for small software consultancy companies is the collective knowledge possessed by their consultants. There have been some studies in the literature on how to harvest and transfer this knowledge, but most studies are aimed at large multinational corporations. In this paper we describe an ongoing research project, aimed at improving knowledge sharing in a small software consultancy company through the use of a method framework in an electronic process guide coupled with an experience repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…They [11] Users should be involved in development [18] Approach to support design activities [22,109] Use of knowledge repositories over time Benefits can be realized quickly, tool remains useful over time, and more benefits accrue over time [70] Tool can be used for different kinds of knowledge than originally intended [33] Empirical studies 6 1 12 0 3 0 3 25 % Distribution, empirical studies 24 4 48 0 12 0 12 100 Lessons learned reports 20 0 9 0 2 1 9 found several distinct ways of using the tool and highlight the importance of informal organization and the social integration of the tool in daily work practices. A more formal approach to knowledge management tools is found in [109], where Skuce describes experiences from applying a knowledge management tool in the design of a large commercial software system.…”
Section: Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…They [11] Users should be involved in development [18] Approach to support design activities [22,109] Use of knowledge repositories over time Benefits can be realized quickly, tool remains useful over time, and more benefits accrue over time [70] Tool can be used for different kinds of knowledge than originally intended [33] Empirical studies 6 1 12 0 3 0 3 25 % Distribution, empirical studies 24 4 48 0 12 0 12 100 Lessons learned reports 20 0 9 0 2 1 9 found several distinct ways of using the tool and highlight the importance of informal organization and the social integration of the tool in daily work practices. A more formal approach to knowledge management tools is found in [109], where Skuce describes experiences from applying a knowledge management tool in the design of a large commercial software system.…”
Section: Systemsmentioning
confidence: 99%
“…The main focus is on the engineering and systems schools. Approach to supporting risk in project management [11] Users should be involved in development [20] Approach to support design activities [24,111] Use of knowledge repositories over time Benefits can be realized quickly, tool remains useful over time, and more benefits accrue over time [72] Tool can be used for different kinds of knowledge than originally intended [35] In [24], Chewar and McCrickard present their conclusions from three case studies investigating the use of their knowledge repository. On the basis of their case studies, they present general guidelines and tradeoffs for developing a knowledge repository.…”
Section: Technocratic Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have contributed to the growth of knowledge management and representation: Semantic Web [5,13,22,48], experience repositories [8,21,23,39], wikis [17,40,43,51,70], process assets libraries [26] and electronic process guides (EPG) [10,12,37,48,49,52]. Some limitations on representing the knowledge of software engineer experts have been found in these works.…”
Section: Related Workmentioning
confidence: 99%
“…Related to this paper, experiences have been connected to electronic process guides (EPGs) (Scott and Jeffery 2003;Kurniawati and Jeffery 2006;Scott and Stålhane 2003;Bjørnson and Stålhane 2005). The type of information kept is mostly development artifacts such as project documentation, templates, and checklists.…”
Section: Background and Related Workmentioning
confidence: 99%